INVESTIGATION OF TROPOSPHERIC RADIO REFRACTIVITY AND OTHER RELEVANT PARAMETERS USING METEOROLOGICAL VARIABLES OVER BAUCHI, NIGERIA - Akpootu, Davidson Odafe; Aminu, Z.; Yusuf, A.; Nouhou, I.; Kola, T. A.; Agidi, O. E.; Salifu, S. I.; Idris, M.; Aliyu, M. A.; Aruna, S. (FUDMA JOURNAL OF SCIENCES, 2024)
The National Aeronautics and Space Administration (NASA) archives were used in this work to obtain the measured monthly average daily temperature, relative humidity, and atmospheric pressure over a 41-years period (1981–2021) for Bauchi (latitude , longitude ) to calculate the monthly tropospheric radio refractivity. The site is located in Nigeria's midland climate zone. We also looked into the variation with other factors, the refractivity gradient, and the percentage contribution of the dry term (Ndry) and wet term (Nwet) radio refractivity. The results showed that during the rainy and dry seasons, respectively, the months of August and February had the highest and lowest average values of radio refractivity, measuring 355.032 (N-units) and 273.255 (N-units), respectively. This suggests that radio refractivity is higher during the rainy season than it is during the dry season. The wet term contributes to the significant fluctuation in radio refractivity values, while the dry term makes up 77.60 % of the total value. The average refractivity gradient estimate was found to be – 40.854 N – units/km suggesting super-refraction propagation for Bauchi indicating that electromagnetic waves are often bent downward towards the earth when the super refraction condition occurs.
Keywords: Bauchi; Meteorological parameters; Percentage contribution; Radio refractivity; Refractivity gradient